2015
DOI: 10.1016/j.bios.2014.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Label free detection of 5′hydroxymethylcytosine within CpG islands using optical sensors

Abstract: Significant research has been invested in correlating genetic variations with different disease probabilities. Recently, it has become apparent that other DNA modifications, such as the addition of a methyl or hydroxymethyl group to cytosine, can also play a role. While these modifications do not change the sequence, they can negatively impact the function. Therefore, it is critical to be able to both read the genetic code and identify these modifications. Currently, the detection of hydroxymethylated cytosine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Detection of methylation patterns in DNA sequences also promises to provide insight into the epigenetic regulation of gene transcription, ultimately controlling cell and organismal phenotype (105). Hawk and Armani (106) reported a microtoroid cavity modified with methylation-specific antibodies and used it to detect methylated DNA in buffer without the need for PCR amplification or fluorescent tagging.…”
Section: Applications Of Optical Resonatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of methylation patterns in DNA sequences also promises to provide insight into the epigenetic regulation of gene transcription, ultimately controlling cell and organismal phenotype (105). Hawk and Armani (106) reported a microtoroid cavity modified with methylation-specific antibodies and used it to detect methylated DNA in buffer without the need for PCR amplification or fluorescent tagging.…”
Section: Applications Of Optical Resonatorsmentioning
confidence: 99%
“…Output can be monitored with a photodetector, measuring current over time. Though the alignment can be arduous, this method allows for highly efficient coupling [e.g., Refs (106, 120)]. ( B ) Grating couplers allow for on-chip coupling without the demands of precise fiber alignment, though at the cost of lower coupling efficiencies.…”
Section: Figurementioning
confidence: 99%
“…The linear regression equation can be expressed as I pa (mA) = 0.51logc (nM) + 1.46 with the correlation coefficient of 0.9975. The limit of detection (LOD) was calculated to be 1.43 pM (S/N = 3), which is lower than that obtained at HPLC-MS/MS analysis (20 pM) [33] and high than that at optical sensor (0.42 pM) [34]. In addition, it has been reported that the content of 5hmC in human urine samples were about 22.6 AE 13.7 nM [33], which is higher than our detection limit.…”
Section: Detection Performancementioning
confidence: 99%
“…Hence there is a growing interest in noninvasive, label-free, real-time, data-rich biosensing systems that measure electrical, optical, magnetic, or mass related properties of the biological sample. Such sensing techniques include surface plasmon resonance spectroscopy [1], electrochemical quartz crystal microbalance measurements [2], optical sensing [3], impedimetric sensing [46], and capacitive sensing [711]. …”
Section: Introductionmentioning
confidence: 99%